Carbon emissions pinch analysis of economic systems - Tan, Raymond Girard R. (Animo Repository, 2018)
Carbon Emissions Pinch Analysis is a variant of Pinch Analysis that was developed for macroscale carbon-constrained energy planning problems. It uses carbon intensity as the measure of quality of energy streams to be allocated within a large-scale system. Since its inception, this method has been applied to various systems at different scales, utilized in different geographic contexts, and also extended to allow different sustainability metrics, such as land and water footprints, to be considered. In this paper, Carbon Emissions Pinch Analysis is further extended by combining it with Input-Output Analysis. This hybrid approach is capable of economy-wide analysis, where the segments of composite curves are comprised of the sectors in an economic system; flow quantities are measures in terms of economic value, while quality is indicated by carbon intensity. After first illustrating this approach to a small pedagogical case study, the methodology is then applied to a case study on the carbon-constrained economic growth of the Philippines. Prospects and limitations of the potential application of this methodology to other cases are also discussed. © 2018 Elsevier Ltd